The Sun, 13 July 2007 - Cheah, Boon Kheng Dr (Sun Media Corp.Sdn.Bhd., 2007)
The MalayanUnion, which the British Labour Government in augurated in post-war Malaya on April 1, 1945, lasted slightly more than two years. Although it was shorted constitutional experiment, it led to dramatic politician development